Conservation, community benefit, capacity buliding and the social economy : a case study of Lutsel K'e and the proposed national park - Bennett, Nathan (2009)
In 2001, 32 years after the Government of Canada initially proposed a national park on the East Arm of Great Slave Lake in the traditional territory of the Lutsel K'e Dene First Nation, Chief Felix Lockhart indicated to Parks Canada that the community was interested in discussing the idea. In 2006, an MOU was signed between the Government of Canada and the Lutsel K'e Dene First Nation that has lead to the withdrawal of an area of 33,525 km2 while studies, negotiations and consultations take place.